Project Cost Performance Analysis Using the Earned Value Method on the Laga Collector's Highway Improvement Project – Bauguia, Timor-Leste - Luis, Laurenco; Tjendani, Hanie Teki; Wulandari, Esti (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
In order to support Laga-Bauguia trade activities, the Ministry of Public Works (PU) is building a road network to the southern region. In its development, there is the development of the Laga-Bauguia Access Road which will be implemented from February 2023 to February 2025. This highway is one of the most important highways because it will connect the north coast area and cross the hills to the Matabian Mountains area which is visited by many tourists. local and foreign. This research aims to analyze the performance of the Laga - Bauguia Highway improvement project in terms of costs and analyze the estimated costs for the remaining work, as well as the cost of completing the Laga - Bauguia Highway improvement project. Every construction project requires control measures in terms of costs, where in carrying out control it is necessary to know in advance the ongoing project performance. One way to determine the cost performance of the project is the Earned Value method. This method can reveal whether the progress in implementing project work is commensurate with the use of part of the budget. By analyzing the concept of Earned Value, the relationship between what has actually been achieved physically and the amount of budget that has been spent can be seen. During the review period in the 8th month, a CPI value of 5.50 was obtained, which means that the actual costs incurred were less than the budget costs. In the 13th month, the CPI value was obtained at 5.50, which means the actual costs incurred were smaller than the budgeted costs.